Perlakuan terhadap Tawanan Perang dalam Hukum Humaniter Internasional dan Hukum Islam - Abidin, Ali Zainal (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
In war, those who become prisoners of war must act as individuals as referred to in the 1949 Geneva Convention III. Meanwhile, according to Article 5, if there is doubt about the status of someone who is at war and falls into his hands. Enemy, that person must remain in custody until his status is determined by a court of competent jurisdiction. In Islam, the rules of Islamic warfare refer to what the Islamic scholars accept in sharia (Islamic law) and fiqh (Islamic law) as laws in Islam that Muslims must follow when fighting each other. Especially in the treatment of prisoners of war and the process of protecting their rights through law. This study uses the standard legal method in which the author examines the provisions of international law and examines all crimes committed by the military against war prisoners of enemy countries. Outside the Abu Ghraib prison, Iraq, which is currently associated with the rights contained in Islamic law. The data collection method in this study uses survey data. There are similarities and principles in the treatment and protection of prisoners of war according to humanitarian law and Islamic law, namely the provisions regarding prisoners of war in Islamic law are in line with the Geneva Convention III of 1949 and Additional Convention I of 1977 which recognize that respect, security guarantees for prisoners of war, and medical care for prisoners of war. According to the principles of management of prisoners of war in the Qur'an, particularly in sura al-Baqarah verse (190) as three principles of international humanitarian law.